2010
DOI: 10.3354/cr00841
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the effects of land-cover changes on surface climate in the Mediterranean region

Abstract: We investigated the impact of land-cover changes on regional climate over the EuroMediterranean area. For this purpose, we compared a control simulation, which employs the presentday vegetation cover, with 2 different potential vegetation distributions performed with the regional climate model RegCM3 for the time period 1981-2000. The simulation results show how land-cover changes are able to modify both the thermodynamics and dynamics of the lower troposphere in central Europe, particularly during summer. Wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 39 publications
2
32
2
2
Order By: Relevance
“…Generally, during summer, less evaporation is permitted in the global model, which adopts a single-layer surface scheme to describe air−land interactions (Roeckner et al 2003). The different surface scheme, together with possible differences in land cover, may contribute to these dissimilarities (Alessandri et al 2007, Anav et al 2010. However, E_A1B also shows slightly lower et during summer.…”
Section: Evaporation (Et)mentioning
confidence: 93%
“…Generally, during summer, less evaporation is permitted in the global model, which adopts a single-layer surface scheme to describe air−land interactions (Roeckner et al 2003). The different surface scheme, together with possible differences in land cover, may contribute to these dissimilarities (Alessandri et al 2007, Anav et al 2010. However, E_A1B also shows slightly lower et during summer.…”
Section: Evaporation (Et)mentioning
confidence: 93%
“…Climate model studies for the temperate regions showed that replacing forests with agriculture or grasslands reduces the surface air temperatures (Bonan, 1997;Bounoua et al, 2002;Oleson et al, 2004) and the number of summer hot days (Anav et al, 2010). Other studies show opposite results, where temperate forests cool the air compared to grasslands and croplands and contribute to higher precipitation rates in the growing season (Copeland et al, 1996;Hogg et al, 2000;Sánchez et al, 2007).…”
Section: Climatic Effects Of Land Use and Land Cover Changementioning
confidence: 87%
“…For example, simplified conceptual models demonstrate that the feedbacks between surface hydrology and the local energy budget support a large variability of the soil-vegetationatmosphere system, especially in water-limited areas where transitions between wet/cool and dry/hot conditions are possible (Baudena et al, 2008). In particular, past studies performed with the same atmospheric model adopted here shown that the variability of maximum surface temperature is sensitive to changes in the land-cover characteristics (e.g., Anav et al, 2010). Therefore, a more accurate representation of land-sea contrast and land cover characteristics adopted for the DD is expected to produce significant deviations from the GCM and the amplification of its unbiased nonstationarity shown in Fig.…”
Section: Discussionmentioning
confidence: 99%